POSPOSISI NI BAHASA JEPANG DAN PADANANNYA DALAM BAHASA INDONESIA - Febra, Sandi; Aibonotika, Arza; Nimashita, Hana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research discusses about postposition ‘ni’ in Japanese and its’ equivalent in Indonesian. The purpose of This research was to describe postposition ‘ni’ and its’ equivalent in Indonesian, and what kind of verbs could accompany postposition ‘ni’. Data in this research is lingual unit in the form of sentence, and clause posposition ‘ni’ collected from Minna no Nihongo Shokyuu I & II and Minna no Nihongo Chuukyuu I. This study used translational equivalent method and distruibution. The results of this research show that postposition ‘ni’ has a variety of forms when equivalent in Indonesian, it could be a preposition pada, dengan, kepada, di, untuk, dari, ke, dalam, oleh and zero, and kind of verbs that could accompany ‘ni’ that is stative verb, punctual verb, movement verb, intransitve, continuative verb, and instantaneous verb. Postposition’ ni’ can be paired with preposition forms in Indonesian.Keywords : postposition, equivalent, verb